Effective Penta Helix Collaboration in Developing Tourism Villages in Sumedang Regency with the Silih Simbeuh Approach - Eeng Sumarna; Ahmad Geohansa; Mulyaningsih (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This qualitative research uses a case study method with data collection through in-depth interviews, participatory observation, and document analysis. Informants include representatives from local government, academia, business, local community, and media involved in tourism management in Citengah. Data were analyzed using thematic analysis. The findings show that all Penta Helix actors have contributed to the management of Citengah Tourism Village, but coordination and synergy are limited due to unclear regulations, low academic involvement in community education, and constraints in business sector investment. The Silih Simbeuh principle has been applied in the local community but has not yet been fully integrated into cross-sector collaboration. To overcome these challenges, the study recommends a more systematic collaboration strategy with stronger regulatory support. This research contributes to the academic understanding of applying the Penta Helix model with local wisdom perspectives and offers practical strategies for managing tourism villages in Indonesia.